Transferrin receptor-targeted theranostic gold nanoparticles for photosensitizer delivery in brain tumors. Issue 5 (18th December 2014) - Dixit, Suraj; Novak, Thomas; Miller, Kayla; Zhu, Yun; Kenney, Malcolm E.; Broome, Ann-Marie
Abstract : TfR-targeted Au NPs may have important therapeutic implications for delivering brain tumor therapies and/or providing a platform for noninvasive imaging. Abstract : Therapeutic drug delivery across the blood-brain barrier (BBB) is not only inefficient, but also nonspecific to brain stroma. These are major limitations in the effective treatment of brain cancer. Transferrin peptide (Tfpep ) targeted gold nanoparticles (Tfpep -Au NPs) loaded with the photodynamic pro-drug, Pc 4, have been designed and compared with untargeted Au NPs for delivery of the photosensitizer to brain cancer cell lines. In vitro studies of human glioma cancer lines (LN229 and U87) overexpressing the transferrin receptor (TfR) show a significant increase in cellular uptake for targeted conjugates as compared to untargeted particles. Pc 4 delivered from Tfpep -Au NPs clusters within vesicles after targeting with the Tfpep . Pc 4 continues to accumulate over a 4 hour period. Our work suggests that TfR-targeted Au NPs may have important therapeutic implications for delivering brain tumor therapies and/or providing a platform for noninvasive imaging.